Modelo pedagógico del Centro Infantil Bilingüe de Colores - Auz Montenegro, Stephanie Gabriela (2018)
We will start by pointing out that the work is a research, which presents an analysis of the pedagogical models of the children's center that have been developed as time has gone by and its historical review. Therefore, it will be indicated which and how many models are applied in the class classroom of the Bilingual Children's Center of Colors of the city of Quito. Different concepts of model, pedagogy, pedagogical model, technique, instrument, methodology, etc. are exposed. In turn, the historical context and its respective authors are described according to the years. After that, there are seven questions, which are found in the 2014 Initial Education Curriculum, these help to discern the most relevant aspects of a pedagogical model and determine which of them it is the best for a teacher to work. To perform the analysis and presentation of findings, the observation form was used, which was feasible and adequate to describe the methodologies used. In addition, the pedagogical criteria included in the file (methodology, resources and evaluation) allowed the description of the results found in the children's center the observation was made to four teachers. An interview (Annex 2) and observations in each classroom were used with instruments for the collection of information. This results in effective results that can be drawn after analyzing them. One of them is that the pedagogical model most used in the institution by teachers is a mixture of constructivist, traditionalist and behavioral schools.